Energy governance as a commons: Engineering alternative socio-technical configurations. (February 2022) - Giotitsas, Chris; Nardelli, Pedro H.J.; Williamson, Sam; Roos, Andreas; Pournaras, Evangelos; Kostakis, Vasilis
Abstract: Transitioning into a sustainable energy system is becoming ever more pressing as the reality of an anthropogenic ecological crisis becomes difficult to ignore. Due to the complexity of the matter, proposed solutions often address the symptoms of the current socioeconomic configuration rather than its core. To conceptualise possible future energy systems, this Perspective focuses on the disconnect between science and technology and engineering studies. On the one hand, this disconnect leads to social science research that passively critiques rather than contributes to tackling societal issues in practice. On the other, it produces technical work limited by the incumbent conceptualisations of economic activity and organisational configurations around production without capturing the broader social and political dynamics. We thus propose a schema for bridging this divide that uses the "commons" as an umbrella concept. We apply this framework on the hardware aspect of a conceptual energy system, which builds on networked microgrids powered by open-source, lower cost, adaptable, socially responsible and sustainable technology. This Perspective is a call to engineers and social scientists alike to form genuine transdisciplinary collaborations for developing radical alternatives to the energy conundrum.